DISKRIMINASI TERHADAP WARGA KETURUNAN TIONGHOA DALAM EMPAT CERITA PENDEK BERTEMA TRAGEDI MEI 1998 - Iwan Sulistiawan (Journal of Innovation Research and Knowledge, 2025)
This research aims to see how four Indonesian short stories(Cong Li di Bulan Mei, Ruang Hampa di Bola Mata, Nio and Tak Ada Mawar di Jalan Raya) depict the acts of discrimination; actions or behaviors that unfairly treat individuals, namely the Indonesian Chinese, especially during May 1998 Riot. Using the sociology approach in analyzing work of fiction, this research tries to see how several restrictions towards the Indonesian Chinese are portrayed in the four short stories, namely restrictions of culture, activities including religious ones, social and political as well as administrative and the violence and criminal acts during the riot. The result shows that all the discriminatory acts are shown by the four short stories, in how the authors use the intrinsic elements, especially plot, characterization as well as language style